Incidence of Heparin resistance after preoperative heparin therapy in patients undergoing open heart surgery - Ali Naeem, Attaullah Khan Niazi, Muhammad Muneeb, Ammar Hameed Khan, Kiran Mazhar, Kanza Sana Umer (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Incidence of Heparin Resistance after preoperative heparin therapy in patients undergoing open heart surgery. Methods: The Prospective Observational study included 124 patients of different heart diseases undergoing open heart surgery, at cardiac surgery department of Punjab Institute of Cardiology; Lahore Pakistan was performed between 5th October 2013 to 16 March 2014. Both genders age 18-75 were included. All those patients who present with diseases other than heart diseases, age <18 and > 75 were excluded in the study. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 16.0. P-value ≤ 0.05 were considered significant. Results: Our results showed that out of 124 patients, 87(70.16%) were male while 37(29.84%) were females. Clinical characteristics i.e. (hypertension, diabetes mellitus, emergency bypass, smoking, alcohol intake, hyperlipidemias, obesity and family history) were insignificantly associated with heparin resistance. The clinical characteristics i.e. (baseline activated clotting time, albumin and cross clamp time) were significantly associated with the development of heparin resistance as (p-value <0.05 .015, .041 and .025 respectively). Conclusion: The results indicate that the incidence of heparin resistance after preoperative heparin therapy was 8.06%.